2018
DOI: 10.1016/j.clim.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Role of the JAK/STAT signaling pathway in regulation of innate immunity in neuroinflammatory diseases

Abstract: The Janus Kinase/Signal Transducers and Activators of Transcription (JAK/STAT) signaling pathway is utilized by numerous cytokines and interferons, and is essential for the development and function of both innate and adaptive immunity. Aberrant activation of the JAK/STAT pathway is evident in neuroinflammatory diseases such as Multiple Sclerosis and Parkinson’s Disease. Innate immunity is the front line defender of the immune system and is composed of various cell types, including microglia, macrophages and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
125
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(142 citation statements)
references
References 154 publications
0
125
1
3
Order By: Relevance
“…The binding pattern of STAT TFs is largely cell type-specific, and individual STAT members often bind in the proximity of cell type-specific TFs (84). Aberrant activation of JAK/STAT signaling in innate immune cells is associated with both multiple sclerosis (MS) and Alzheimer's disease (AD) (85).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E Nmentioning
confidence: 99%
“…The binding pattern of STAT TFs is largely cell type-specific, and individual STAT members often bind in the proximity of cell type-specific TFs (84). Aberrant activation of JAK/STAT signaling in innate immune cells is associated with both multiple sclerosis (MS) and Alzheimer's disease (AD) (85).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E Nmentioning
confidence: 99%
“…STAT families are downstream regulator of JNK pathway and involved in sequential dimer formation, nuclear translocation, binding to specific DNA sequences, and regulating cell proliferation . Studies indicated activation of STATs involved in microglia/macrophage polarization . STAT1 is related to M1 response, while STAT3 is related to M2 response, especially M2c subcategory, which is associated with tissue repair, extracellular matrix repair, and de‐activation of M1/Th1 immune response .…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Studies indicated activation of STATs involved in microglia/macrophage polarization. [35][36][37] is related to M1 response, while STAT3 is related to M2 response, especially M2c subcategory, which is associated with tissue repair, extracellular matrix repair, and de-activation of M1/Th1 immune response. [38][39][40] Thus, we hypothesized whether HBOP regulates microglia/macrophage polarization through those signal pathways.…”
Section: Discussionmentioning
confidence: 99%
“…; Groner & von Manstein ; Yan et al . ). Many parallels have been identified between human and Drosophila JAK/STAT signaling, including neoplastic growth in JAK‐mutated flies (Trivedi & Starz‐Gaiano ).…”
Section: Introductionmentioning
confidence: 97%
“…The Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway promotes cytokine signaling by regulating gene expression, and is mediated by transcription factors such as NF-κB and activator protein 1 (AP-1). Owing to the direct control of cytokines, such as interleukins, interferons, and growth factors, the JAK/STAT pathway is central to cancer and inflammatory diseases (Banerjee et al 2017;Groner & von Manstein 2017;Yan et al 2016). Many parallels have been identified between human and Drosophila JAK/STAT signaling, including neoplastic growth in JAK-mutated flies (Trivedi & Starz-Gaiano 2018).…”
Section: Introductionmentioning
confidence: 99%